Importance of work engagement in primary healthcare - Polona Szilvassy; Klemen Širok (BMC, 2022)
Abstract Background Work engagement is crucial for quality care at the primary healthcare level. This is especially true during the Covid-19 pandemic, as it has effects on the community from both a health and economic point of view. For example, inadequate work engagement can lead to fewer referrals to the secondary healthcare level. This study aims to examine the work engagement level in a public healthcare organisation at the primary healthcare level to further explore the role of work environment characteristics. The study addresses a research gap in the field of primary healthcare and emphasises the importance of managing the factors promoting work engagement. The future of healthcare will be strongly shaped by population ageing and Covid-19 disruption, which have created unpredictable and unfavourable working situations. Method A descriptive, cross-sectional, correlational design was used including the Utrecht Work Engagement Scale with a non-probabilistic availability sample of 630 employees of the Community Health Centre Ljubljana, Slovenia, in 2018. The role of the work environment was observed by applying the job resources concept adapted to the context of the observed organisation. Results Work engagement in the observed organisation is higher compared to previous research. The research confirmed that job resources play an important role in employees' work engagement. The high level of work engagement of the home care nursing employees coupled with the significant proportions of unengaged in the management of the organization also caught our attention. This difference highlights the importance of the leadership style, career choices and employment process that exist in an institution. Conclusion The study has important implications for healthcare management at the primary level for unlocking the work engagement by 'managing' the factors stimulating work engagement. The hidden potential is especially large in so called 'soft areas', such as leadership style, communication and organisational climate, which are also less expensive to manage than other aspects of the work environment.